Comparative Study of Mangrove Ecotourism in Probolinggo City - Adiningtyas, Cahyarani (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2025)
Probolinggo City has a large coastal area. The vast coastal area is utilized as mangrove ecotourism. Bee Jay Bakau Resort (BJBR) and Permata Beach are well-known mangrove ecotourism. The two mangrove ecotourism has a significant difference in terms of visitors. This factor is a serious concern for managers and will be an evaluation study. This research aims to 1) Comparing the potential of mangrove ecotourism; and 2) Comparing existing conditions in both mangrove ecotourism. The method used is descriptive qualitative method with snowball sampling approach and source triangulation technique. This research uses primary data based on the results of observations and interviews, while secondary data through literature studies. This research uses 4A analysis and analysis of city image elements according to Lynch Theory. The results of the study explain that the potential of the two mangrove ecotourisms is quite good even though they have different development focuses. Not only that, physical and non-physical aspects such as character, identity and city image must continue to be considered in development, it aims not to leave the identity of the city of Probolinggo.